ЧИЗМАЧИЛИК ФАНИДАН МУСТАҚИЛ ТАЪЛИМНИ ТАШКИЛ ЭТИШГА ҚАРАТИЛГАН ИННОВАЦИОН ТАЪЛИМ ВОСИТАЛАРИ - Тураев, Х.А. (SCIENCE and SOCIETY, 2023)
In this article, innovative educational tools aimed at organizing lessons and extracurricular self-study on the subject of The drawings are given practical recommendations with a methodological basis on handouts, visual graphic images, creative tasks, 3D animation, mobile applications, video tutorials, author's channels in social networks and non-traditional test questions. It also provides reasonable information about the technical equipment that will be necessary when using these learning tools in self-study.
Keywords: innovative; education tool; independent learning; creative task; 3D animation; video lessons; mobile application; visual graphic image; social network; non-traditional test